(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
The existentialism appears as opposite to the tradicional philosophical systems and is insinuated as irrational, subjective and emotional. Although referentes to existentialism tend to be included within European thought, the researchers investigated, on a narrative scale, “existentialism elements” in Latin American literature, including Venezuela. For this aim, works of the Venezuelan writer Renato Rodríguez were analyzed, a writer whose works face us with the dynamics between systems of philosophical thought as directives for life, and the search for experiences such as confirmation of the human existence